How Far Scientific is Snakebite Prevention and First Aid Treatment in School Textbook? - Fairouz, Faiha; Rashid, Rumana; Sayeed, Abdullah Abu (Bangladesh Journal of Medicine, 2019)
Background: Snakebite is an old health problem in rural areas. In Bangladesh, the snakebite issue is included in school syllabus, in curriculum since long time, so that people can take/get immediate first aid treatment and can prevent snakebite. The success of snakebite treatment depends more on providing first aid treatment immediately after snakebite by learning and by sending the patients quickly to hospital. Snakebite is a preventable health problem indeed. If it can be prevented the rate of snakebite will also decrease. In the recently published snake bite management Guideline by WHO it has been targeted to reduce 50% of mortality & disability due to snakebite by 2030.1 Methods: a. The snakebite topic or issue has been thoroughly reviewed in the secondary and higher secondary school books. b. National Guidelines on snakebite in providing/ giving first aid treatment has been reviewed.2 c. The correlation between the topic to learn the subject and the national guidelines have been reviewed and given taken into account. d. The similarity or correlation between the national guidelines and the topic in the prevention of snakebite in the book have been observed & reviewed. It was a descriptive/narrative research study. Results: In the book of class IV in Primary and Secondary level students, ‘Elementary Science, (‘Prathomiik Bigghan’) page no. 86 and in book of class VIII Home Science (‘Gharjhastha Biggan’) page no. 16 the Snakebite issue/topic is mentioned.2,3 There are 22 information on the first aid/primary treatment of Snakebite among which 5 (five) are nonscientific rather harmful. (Table & Picture) Bangladesh J Medicine Jan 2020; 31(1) : 39-40